10
$\begingroup$

I thought of following situation/problem, and was surprised that the solution did not jump out at me. Fix a positive integer $n$ and let $V_n$ be the finite-dimensional vector space of all polynomials of degree $\leq n$ with real coefficents. Make $V_n$ into a inner product space with respect to $$ \langle p,q \rangle = \int_{-1}^1 p(x) q(x) \ dx.$$ Now, fix some point $x_0 \in \mathbb{R}$ and consider the linear functional \begin{align*} \varphi_{x_0} : V_n \to \mathbb{R} && \varphi_{x_0}(p) = p(x_0). \end{align*} Because we are in an inner product space, there is a unique polynomial $p_{x_0,n}$ such that \begin{align*} \varphi_{x_0}(p) = \langle p_{x_0,n},p \rangle =\int_{-1}^1 p_{x_0,n}(x) p(x) \ dx && \forall p \in V_n. \end{align*}

Question: What is this polynomial!?

One approach would be to apply the Gramm-Schmidt procedure to $1,x,\ldots,x^n$ to get an orthonormal basis $p_0,p_1,\ldots,p_n$ for $V_n$ and then calculate $\varphi_{x_0}$ on this basis. The required vector should be then $\sum_{i=0}^n \varphi_{x_0}(p_i) p_i$, but I am hoping for a more enlightening representation.

$\endgroup$
  • $\begingroup$ You seem to be looking for the delta "function" in that vector space. Wont be a finite linear combination of polynomials, safe to say. $\endgroup$ – Macavity Oct 16 '15 at 15:56
  • $\begingroup$ @Macavity: Note I am only asking for $\int_{-1}^1 p_{x_0,n} (x) p(x) \ dx = p(x_0)$ when $p$ is a polynomial of degree $\leq n$. $\endgroup$ – Mike F Oct 16 '15 at 16:37
  • 3
    $\begingroup$ Doesn't seem to be nice. The reproducing kernel is $k_n(x,y)=\sum_{k=0}^n \frac{2k+1}{2}P_k(x)P_k(y)$, where $P_k$ are the Legendre polynomials. I calculated a few: $k_1(x,y)=\frac{1+3xy}{2}$, $k_2(x)=\frac98+\frac32xy+\frac{15}{8}(x^2+y^2)+\frac{45}{8}x^2y^2$... no enlightement here. But then again, we shouldn't expect a nicer form for a reproducing kernel than one for an orthonormal basis. A search brought up this book, section 8.3 (pp 94-) discusses such kernels a bit. $\endgroup$ – user147263 Oct 18 '15 at 6:15
  • $\begingroup$ There's a chance that $k_n(x,0)$ can have a nicer form; it's a certain alternating weighted sum of the Legendre polynomials of even degrees... $\endgroup$ – user147263 Nov 1 '15 at 2:15
  • 2
    $\begingroup$ If anyone's interested in seeing what such polynomials look like, I posted some pictures here. $\endgroup$ – user147263 Nov 1 '15 at 17:46
3
+100
$\begingroup$

This will be not a very nice and effective answer but gives a more or less direct formula for the polynomial $\varphi_{x_0}$.

We will repeat the proof for Rodriguez's formula for the Legendre polynomials. Let $q_0,q_1,q_2,\ldots,q_{n+1}$ be the sequence of polynomials such that $$ q_0 = \varphi_{x_0}; \qquad q_{k+1}' = q_k \quad\text{and}\quad q_{k+1}(-1)=0 \quad (k=0,1,\ldots,n). $$ We will compute the polynomial $q_{n+1}$.

The condition, applied to the polynomial $(1-x)^k$ (with $0\le k\le n$) yields $$ \int_{-1}^1 \varphi_{x_0}(x) \cdot (1-x)^k dx = (1-x_0)^k. $$ Integrating by parts $k$ times, \begin{align*} (1-x_0)^k &= \int_{-1}^1 q_0(x) \cdot (1-x)^k dx = \underbrace{\Big[q_1(x) \cdot (1-x)^k\Big]_{-1}^1}_0 + \int_{-1}^1 q_1(x) \cdot k(1-x)^{k-1} dx = \\ &= k\int_{-1}^1 q_1(x) \cdot (1-x)^{k-1} dx = k(k-1)\int_{-1}^1 q_2(x) \cdot (1-x)^{k-2} dx = \dots = \\ &= k! \int_{-1}^1 q_k(x) dx = k! \cdot q_{k+1}(1) = k! \cdot q_{n+1}^{(n-k)}(1). \end{align*} Therefore, $$ q_{n+1}^{(n-k)}(1) = \frac{(1-x_0)^k}{k!}. $$

The $n$th Taylor-polynomial of $q_{n+1}$ around $1$ is $$ \sum_{k=0}^n \frac{q_{n+1}^{(n-k)}(1)}{(n-k)!}(x-1)^{n-k} = \sum_{k=0}^n \frac{(1-x_0)^k}{k!}(x-1)^{n-k} = \\ = \frac1{n!} \sum_{k=0}^n \binom{n}{k}(1-x_0)^k(x-1)^{n-k} = \frac{(x-x_0)^n}{n!} $$ so $$ q_{n+1}(x) \equiv \frac{(x-x_0)^n}{n!} \pmod{(x-1)^{n+1}}. \tag1 $$ By the condition $q_1(-1)=q_2(-1)=\ldots=q_{n+1}(-1)=0$ we know that $$ q_{n+1}(x) \equiv 0 \pmod{(x+1)^{n+1}}. \tag2 $$ Since $\deg q_{n+1}\le 2n+1$, by the Chinese Remainder Theorem, the congruences (1) and (2) uniquely determine $q_{n+1}$.

A solution of the congruences (1) and (2), but with higher degree is $$ \left(\bigg(\frac{x-1}2\bigg)^{n+1}-(-1)^{n+1}\right)^{n+1} \cdot \frac{(x-x_0)^n}{n!}. $$ Dividing with remainders, we can see that $$ q_{n+1}(x) = \left(\bigg(\frac{x-1}2\bigg)^{n+1}+(-1)^n\right)^{n+1} \cdot \frac{(x-x_0)^n}{n!} \mod (1-x^2)^{n+1} $$ and therefore $$ \varphi_{x_0}(x) = \left( \left(\bigg(\frac{x-1}2\bigg)^{n+1}+(-1)^n\right)^{n+1} \cdot \frac{(x-x_0)^n}{n!} \mod (1-x^2)^{n+1}\right)^{(n+1)} . $$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.